Eu3+-Doped Y3−xSmxAl5O12 garnet: synthesis and structural investigation. (19th January 2018) - Pavasaryte, L.; Katelnikovas, A.; Klimavicius, V.; Balevicius, V.; Momot, A.; Van Bael, M.; Hardy, A.; Kareiva, A.
Abstract : Sm 3+ -Doped and Eu 3+ /Sm 3+ - co -doped yttrium aluminium garnets (YAG) have been synthesized by an environmentally friendly sol–gel method. Abstract : Sm 3+ -Doped and Eu 3+ /Sm 3+ - co -doped yttrium aluminium garnets (YAG) have been synthesized by an environmentally friendly sol–gel method. The results of X-ray diffraction (XRD) analysis of the powders sintered at 1000 °C showed the high purity of the end products with formation of monophasic compounds. The phase composition of the samples was also investigated by FTIR spectroscopy. The microstructural features of the polycrystalline samples were studied by scanning electron microscopy (SEM). The local environments of Eu 3+ and Sm 3+ activator ions in the garnet crystal structure compounds were investigated by nuclear magnetic resonance (NMR) and Raman spectroscopy. The luminescence properties were discussed using the results from photoluminescence (PL) study. The effective concentration of Sm in YAG was estimated and optimum ratio between two activators (Eu 3+ and Sm 3+ ) was analysed. The correlation between structural features and luminescence was determined. With a constant amount of samarium in Y2.9 Sm0.1 Al5 O12 :Eu garnet the strongest luminescence was determined in the sample with 1% of europium when characteristic excitation for europium was used.